Income Shifting and Management Incentives - Ortmann, Regina; Schindler, Dirk

Wem gehört das Meer? Globale Ressourcen und die dritte UN-Seerechtskonferenz (1968–1994) - Sackel, Johanna

Sarah Ihden, Katharina Dreessen u. Robert Langhanke (Hgg.): Studien zur mittelniederdeutschen und frühneuhochdeutschen Sprache und Literatur, Hildesheim, Zürich u. New York: Olms 2021. - Wallmeier, Nadine (PBB)

Digitization in Catalysis Research: Towards a Holistic Description of a Ni/Al2O3Reference Catalyst for CO2Methanation - Weber, Sebastian; Zimmermann, Ronny T.; Bremer, Jens; Abel, Ken L.; Poppitz, David; Prinz, Nils; Ilsemann, Jan; Strübbe, Sven; Yang, Qingxin; Pashminehazar, Reihaneh; Monaco, Federico; Cloetens, Peter; et al. (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Low-code experimentation on software products - Gottschalk, Sebastian; Bhat, Rakshit; Weidmann, Nils; Kirchhoff, Jonas; Engels, Gregor (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)

 Zeitschrift für Romanische Sprachen und ihre Didaktik

 Zeitschrift für Romanische Sprachen und ihre Didaktik

High resolution off resonant spectroscopy as a probe of the oxidation state - Nowakowski, Michal; Kalinko, Aleksandr; Szlachetko, Jakub; Fanselow, Rafał; Bauer, Matthias (Journal of Analytical Atomic Spectrometry)
The direct conversion between HEROS-XES and XANES edge position (E0) without need of measuring absorption spectra.
Keywords: Spectroscopy; Analytical Chemistry

Asymptotic stability of spatial homogeneity in a haptotaxis model for oncolytic virotherapy. - Tao, Youshan; Winkler, Michael (Proceedings of the Royal Society of Edinburgh Section A: Mathematics)

Nonnegative solutions to a doubly degenerate nutrient taxis system - Li, Genglin; Winkler, Michael (Communications on Pure and Applied Analysis)

"Wir sind gekommen, doch wir sind gar nicht da" - Mythologische Formationen von Macht und Gewalt in Aischylos' "Die Schutzfllehenden" und Elfriede Jelineks "Die Schutzbefohlenen" - Böker, Ines (Mythos und Postmoderne. Mythostransformationen und mythische Frauen in zeitgenössischen Texten)

Armutssensibilität als religionspädagogische Herausforderung – Spannungsverhältnisse im fachdidaktischen Transfer der 'Option für die Armen' - Uppenkamp, Vera (Wissenstransfer. Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung)

Armutssensibilität im inklusiven Religionsunterricht - Uppenkamp, Vera (Handbuch der Religionen (73. Ergänzungslieferung))

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Quantum-state creation in nonlinear-waveguide arrays - Hamilton, Craig S.; Christ, Regina; Barkhofen, Sonja; Barnett, Stephen M.; Jex, Igor; Silberhorn, Christine (Physical Review A)

Am Ende siegt die Liebe. Wie M. Night Shyamalans „The Happening“ im Zuge der Coronapandemie neu gesehen werden kann - Pinsch, Jan Christian (Pandemie im Film. Religiöse und ästhetische Transformationen in der Populärkultur)

Von der Corona-Realität eingeholt. Verschwörungserzählungen und Endzeiterwartungen in der Serie „Sløborn“ - Pinsch, Jan Christian (Pandemie im Film. Religiöse und ästhetische Transformationen in der Populärkultur)

Rezension zu Gerhard Kampe/Thomas Kampe (Ed.), beyond forgetting. persecution/exile/memory. transdisciplinarity in design, perfomance and education, Göttingen 2021 - Pinsch, Jan Christian; Lerke, Stephanie (theologie.geschichte. Zeitschrift für Theologie und Geschichte)

A Method for Predicting Workarounds in Business Processes - Sven, Weinzierl; Bartelheimer, Christian; Zilker, Sandra; Beverungen, Daniel; Matzner, Martin (Proceedings of the 26th Pacific Asia Conference on Information Systems (PACIS))

Inclusive science teaching in primary schools and its didactic-diagnostic potential. Single Paper. Porto International Conference on Research in Education 2022 (ICRE 2022) - Franzen, Katja; Blumberg, Eva; Schroeder, René; Reh, Anne; Miller, Susanne; Kottmann, Brigitte